The Effects of Dietary Rosemary (Rosmarinus officinalis L.) Oil Supplementation on Performance, Carcass Traits and Some Blood Parameters of Japanese Quail Under Heat Stressed Condition - Ciftci, Mehmet; Simsek, Ulku Gulcihan; Azman, Mehmet Ali; Cerci, Ibrahim Halil; Tonbak, Fadime (Kafkas Univ, Veteriner Fakultesi Dergisi, 2013)
In this study, the effects of rosemary (Rosmarinus officinalis L.) oil supplementation to diet were investigated on performance, carcass traits and some blood parameters of Japanese quails exposed to a high ambient temperature of 34 degrees C. A total of 180 fifteen-day-old quails were divided into 6 treatments consisting of 10 birds of 3 replicates. All groups were balanced according to initial live weight and gender. Birds were kept in wire cages in temperature-controlled room at either 22 degrees C for 24 h/d (thermo neutral-TN) or 22 degrees C for 16 h/d and 34 degrees C (heat stress-HS) for 8 h/d (from 9:00 to 17:00) during the study. Trial was conducted as a 2x3 factorial arrangement. Birds were fed either a basal (control) diet (TN and HS) or the basal diet supplemented with 125 or 250 ppm of rosemary oil. The highest final live weight was observed in 250 ppm rosemary oil under the TN condition and the lowest was in control group of HS. HS condition affected negatively on quail live weight (P<0.05), but the effect of rosemary oil on this parameter was not significant (P>0.05). Live weight gain and feed intake were not significantly different among the treatment groups (P>0.05). Feed conversion ratio was better in rosemary oil groups than control groups in both environmental conditions (P<0.01). Heat stress deteriorated carcass yield (P<0.01). The highest hot and cold carcass yield (g/100 g of body weight) was observed in 250 ppm rosemary oil added group under the TN condition, but this difference did not significant. Birds kept in HS conditions had greater glucose level than hens kept in TN conditions (P<0.01). Rosemary oil decreased blood glucose level, especially in 250 ppm group of HS (P<0.05). Total, HDL, LDL cholesterol and triglyceride levels were not significantly different among the treatment groups (P>0.05). In conclusion, rosemary oil supplementation reduced the negative effects of heat stress. Rosemary oil could be considered as a potential natural feed additive, following further studies.
Sıcaklık stresi altındaki japon bıldırcınlarında karma yeme İlave edilen biberiye (Rosmarinus officinalis L.) ya?ının performans, karkas özellikleri ve bazı kan parametreleri üzerine etkileri
Keywords: Rosemary oil; Performance; Carcass traits; Blood parameters; Quail; Heat stress